Complete response in hepatocellular carcinoma with lymph node metastasis by combination therapy of atezolizumab and bevacizumab: a case report - Sang Youn Hwang; Sun Mi Lee; Jeong Woo Lim; Gi Jung Jeon; Hye Won Lee (Korean Liver Cancer Association, 2021)
Sorafenib is the oldest first line systemic treatment in patients with advanced hepatocellular carcinoma (HCC) and has been used exclusively for nearly 10 years. The superiority of administering a combination of atezolizumab plus bevacizumab (AteBeva) compared to sorafenib as first line systemic treatment for unresectable HCC was recently proven during the IMbrave150 Phase III randomized trial. While clinicians can expect improved responses and treatment outcomes due to the good results of the IMbrave 150 trial, they must also consider that atezolizumab can cause various immune-related adverse events (IrAEs). Based on the above suggestions, we herein present a case of HCC with lymph node metastasis who achieved complete remission following treatment with AteBeva and developed an IrAE (adrenal insufficiency). Further study of real-life data regarding combination therapy with AteBeva is needed to manage patients with advanced HCC.